Comparison of models for the selection of cloud computing resources - Haurech, Hugo Rolando (2020)
Fil: Haurech, Hugo Rolando. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas Químicas y Naturales; Argentina.